2007
DOI: 10.1038/sj.bmt.1705729
|View full text |Cite
|
Sign up to set email alerts
|

HLA-identical haematopoietic stem cell transplantation for acute leukaemia in children: less relapse with higher biologically effective dose of TBI

Abstract: To examine relapse, survival and transplant-related complications in relationship to disease-and pre-treatment-related characteristics, we evaluated 132 children, who consecutively received an allogeneic HLA-identical SCT for acute leukaemia in our centre: ALL in first remission (n ¼ 24), ALL in second remission (n ¼ 53) and AML in first remission (n ¼ 55). The source of the stem cells was bone marrow in all but three cases. Most patients (89%) were pre-treated with cyclophosphamide and an age-related dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…STBI and hyperfractionated schedules with higher biological effective dose values than 9.9 Gy administered in three fractions were associated with a lower risk of relapse, concurring with other reports. 33,34 Lung dose did not impact upon OS or relapse in multivariate analyses. Even though shielding generally limits it to 75-80% of the total dose so as to reduce the risk of interstitial pneumonia and transplant-related mortality, in some series the ensuing reduced dose to rib BM was linked to a higher incidence of relapse.…”
mentioning
confidence: 99%
“…STBI and hyperfractionated schedules with higher biological effective dose values than 9.9 Gy administered in three fractions were associated with a lower risk of relapse, concurring with other reports. 33,34 Lung dose did not impact upon OS or relapse in multivariate analyses. Even though shielding generally limits it to 75-80% of the total dose so as to reduce the risk of interstitial pneumonia and transplant-related mortality, in some series the ensuing reduced dose to rib BM was linked to a higher incidence of relapse.…”
mentioning
confidence: 99%
“…Even though fractioned TBI seems to give superior results regarding relapse and OS rates while limiting adverse effects on the other tissues comparing to single-dose TBI, the huge concerns regarding secondary malignancies and growth, hormonal and metabolic disorders still remain crucial, particularly in pediatric population with expected long-time survival. 26,28,34 Some alternative regimens have been used and reported but failed to strongly demonstrate advantage because of a too small cohort or a higher number of early relapse and regimen-related deaths. 29,32,[35][36][37] Much progress was done in the HSCT field from 1990s: improvement in HLA typing, improvement of supportive care, more available immunosuppressive drugs, improvement in laboratory cellular therapy settings, better understanding and monitoring of minimal residual disease.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive effect was required to ensure engraftment. 4,27,28 Historically, combination of CY (Cy 120 mg/kg) and TBI was the most used conditioning regimen. 25,28,29 Radiation-free regimen had been proven effective for eradication of leukemia and sufficiently immunosuppressive for engraftment in HLA-matched sibling transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of acute GVHD decreased relapse risk in AML in more than one trial supporting a GVL effect, although the correlation is not quite as strong as in chronic myeloid leukemia (CML). 6,7 The timing of relapse after initial therapy was criticalsurvival was 21% after early (o1 year) and 48% after late relapse. 8 Although not prospectively studied, a retrospective registry review reported similar outcomes in young children (o18 months) following HLA-matched sibling or unrelated donor transplantation in CR1 (3-year survival 54 and 49% respectively).…”
Section: Autologous Hsct For Amlmentioning
confidence: 99%